SECURITY DYNAMICS OF SOUTHEAST ASIA: THE ROLE OF THE UK AND ITS IMPLICATIONS ON REGIONAL SECURITY - Pratita, Chika Kirana Budi (Journal of Social Political Sciences, 2022)
Post-Brexit, Britain completely overhauled its foreign policy framework by adopting a ’Global Britain’ strategy with the aim of demonstrating global leadership. The UK said that there had been geopolitical and geoeconomics shifts, including the rise of China’s power and the increasing importance of the Indo-Pacific for global prosperity and security as well as the potential for new markets to emerge and the growth of the global middle class. In realizing the UK’s existence in the world, especially in the Indo-Pacific region, the UK considers the strategic position of the Southeast Asia region which is included as part of the four pillars of British foreign policy. Southeast Asia has become an arena for the struggle for the influence of global powers, especially China and the United States. Changes in British Foreign Policy which focuses on the Southeast Asia region will certainly have strategic consequences in the region, especially regional security, especially the South China Sea Dispute which involves most of the ASEAN member countries. The problem raised in this study is how the dynamics of security in the Southeast Asia region after the change in the focus of British foreign policy to Southeast Asia and its impact on regional security. The writing of this article uses qualitative research methods to write to describe the complexity of regional security through patterns of relations between countries in the region and countries outside the region, as well as the role of global powers.